Effect of L-Glutamine Supplementation on Electromyographic Activity of the Quadriceps Muscle Injured By Eccentric Exercise - Rahmani Nia, Farhad (Mashhad University of Medical Sciences, 2013)
Objective(s): The purpose of the present study was to examine the effects of L-glutamine on electromyographic (EMG) activity of the quadriceps muscle injured by eccentric exercise (EE). Materials and Methods: Seventeen healthy men (age: 22.35±2.27 yr; body mass: 69.91±9.78 kg; height: 177.08±4.32 cm) were randomly and double-blind study with subjects assigned to either an L-glutamine supplementation (n=9) or placebo (n=8) group. The subjects in two groups were asked to take three times during a week for 4 weeks. Each subject was screened for dietary habits before inclusion into the study. Participants performed 6 set to exhaustion eccentric leg extensions at 75% of 1RM and rest intervals were 3 min among sets. Pain Assessment Scale (PAS), EMG activity and range of motion (ROM) measurements were taken before exercise protocol and 24 and 48 hr afterwards. Results: There was no statistically significant difference between groups in perceived muscle soreness (SOR), ROM and EMG activity (P < 0.05). Conclusion: The results indicate that L-glutamine supplementation has no significant effect on muscle injury markers in between groups, although glutamine supplementation attenuated delayed onset muscle soreness (DOMS) effects in sup group.